Enhancing Rumen-Undegradable Protein via Processing Techniques in a Dual-Flow Continuous Culture System - Loregian, K. E.; Silva, M. J.; Dourado, S. B.; Guimarães, J. [UNESP]; Amâncio, B. R.; Magnani, E.; Silva, T. H.; Branco, R. H.; Benedeti, P. Del Bianco; Paula, E. M. (MDPI, 2025)
The use of processing techniques to increase the rumen-undegradable protein (RUP) content of protein meals aims to enhance the nutritional performance of high-performance animals. This study evaluated the effects of various processing techniques applied to peanut and cottonseed meals on ruminal parameters using a dual-flow continuous culture system. These two feeds were individually analyzed in two experiments, each one using five fermenters (1297 ± 33 mL) in a 5 × 5 Latin square arrangement with five periods of 10 d each, with 7 d for diet adaptation and 3 d for sample collections. Five treatments were evaluated in each experiment: no processed meal (control); meal thermally treated in an autoclave with xylose (autoclave); meal thermally treated in a conventional oven with xylose (oven); meal thermally treated in a microwave with xylose (microwave); and meal treated with tannin (tannin). All diets contained 60% concentrate (corn, minerals, and processed meal). Fermenters were fed 55 g of dry matter per day, divided equally into two meals at 06:00 and 18:00 h. The solid and liquid dilution rates were adjusted daily to 5.5% and 11% per hour, respectively. On days 8, 9, and 10, 500 mL samples of solid and liquid digesta effluent were collected, mixed, homogenized, and stored at −20 °C. Subsamples of 10 mL were preserved with 0.2 mL of a 50% H2SO4 solution for later determination of NH3-N and volatile fatty acids. Microbial biomass was isolated from the fermenters for chemical analysis at the end of each experimental period. Data were analyzed using the MIXED procedure in SAS with a significance level of α = 0.05. Regarding cottonseed meal, the tannin treatment tended to have a lower true digestibility of DM compared to the control, autoclave, and oven treatments (p = 0.09). Additionally, tannin fermenters exhibited a lower apparent digestibility of CP compared to all other treatments (p = 0.04). The tannin and microwave treatments resulted in the highest flow of dietary nitrogen and the lowest supply of RDP-N (p < 0.01). The control treatment had a greater flow of NH3-N compared to other treatments (p < 0.01). Regarding peanut meal, the autoclave and tannin treatments exhibited the highest acetate concentration (p = 0.03) and the lowest apparent digestibility of CP (p < 0.01). The tannin treatment increased the RUP content without impairing ruminal fermentation and exhibited a greater supply of RDP-N compared to all other treatments (p = 0.02). No significant differences were observed for the other digestibility and fermentation parameters (p > 0.20). Our results indicate that tannin inclusion and microwave processing were the most effective methods for reducing the protein fraction available in the rumen for cottonseed meal. Additionally, tannin inclusion increased the RUP in peanut meal without negatively affecting ruminal fermentation.
Keywords: beef cattle; cottonseed meal; nitrogen; peanut meal